2004
DOI: 10.1111/j.1533-8525.2004.tb02301.x
|View full text |Cite
|
Sign up to set email alerts
|

Doing “Real Family Values”: The Interpretive Practice of Families in the GLBT Movement

Abstract: This article considers how a social movement group in the Gay, Lesbian, Bisexual, and Transgender (GLBT) movement engages in discursive contention with the Religious Right over the meaning of traditional family values. By utilizing an understanding of framing as interpretive practice, we return to a more active conceptualization of framing and illustrate how the meaning making of PFLAG (Parents, Families, and Friends of Lesbians and Gays), though bound by the dominant discourse of traditional family values, ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 17 publications
1
27
0
2
Order By: Relevance
“…Whereas previous studies have shown that religious (Erzen ) and LGBTQ (Broad et al. ) movements may be forced to shift their tactics in relation to broader societal changes, they have generally left the ways larger social patterns influence dominant religious discourses unexplored (but see Thomas and Olson ). LDS elites, however, constructed homosexuality in relation to shifting societal, religious, and LGBTQ attitudes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas previous studies have shown that religious (Erzen ) and LGBTQ (Broad et al. ) movements may be forced to shift their tactics in relation to broader societal changes, they have generally left the ways larger social patterns influence dominant religious discourses unexplored (but see Thomas and Olson ). LDS elites, however, constructed homosexuality in relation to shifting societal, religious, and LGBTQ attitudes.…”
Section: Resultsmentioning
confidence: 99%
“…2010) and sources of moral authority utilized by evangelical elites in Christianity Today (Thomas and Olson ) have indeed shifted in relation to the expansion of LGBTQ rights, that public attitudes about homosexuality have undergone relatively similar shifts (Loftus ), and that LGBTQ movement organizations, like Parents, Friends, and Families of Lesbians and Gays, have adopted similar family values discourses to advocate for sexual equality (Broad et al. ).…”
Section: Problematizing Homosexualitymentioning
confidence: 99%
“…Sumerau and Schrock () discuss LGBTQ Christians who “queered fashion,” “embraced intimacy,” and “transgendered demeanor” in order to navigate conflicts between sexuality and religion. According to Broad, Crawley, and Foley (), parents of LGBTQ children use the discourse of “ real family values” to collectively frame themselves as good parents and parents of children who threaten others' notions of what constitutes acceptable family and sexuality.…”
Section: Identity Dilemmasmentioning
confidence: 99%
“…Despite its stated mission to work on policy, advocacy and education, researchers frequently describe PFLAG as mainly adopting a support group model (Broad, Crawley, & Foley, 2004; Fields, 2001). PFLAG uses parents’ personal testimonies and the support group model to foster its social movement goals of civil rights for sexual minorities (Broad et al, 2004; Fields, 2001). Importantly, although PFLAG has strong ties to the gay and lesbian rights movement, its primary focus has never been one of arguing for sexual rights.…”
mentioning
confidence: 99%
“…Importantly, although PFLAG has strong ties to the gay and lesbian rights movement, its primary focus has never been one of arguing for sexual rights. Its discursive terrain has always been “of and about families and religious values” (Broad et al, 2004, p. 513). PFLAG offers parents the possibility of making their children (and themselves) into “normal queers” and normal families with family values (Broad et al, 2004; Fields, 2001).…”
mentioning
confidence: 99%